Developments in the Internal Affairs of the Patriarchate of Jerusalem in the Aftermath of the Bulgarian Schism (1872–1877) - Maria Litina (Zeszyty Cyrylo-Metodiańskie)
The paper examines material from the Archive of the Patriarchate of Jerusalem concerning internal developments in the Patriarchate and the Brotherhood of the Holy Sepulchre in the aftermath of Patriarch Cyril II’s deposition from the patriarchal throne as a result of his refusal to sign, under Russian pressure, the tomos of the Ecumenical Patriarchate condemning the independent Bulgarian Exarchate. Original title in Bulgarian: Един непознат аспект на българската схизма: Кирил II и неговото падане от патриаршеския трон на Йерусалим (1872–1877).